Implementasi Model PjBL dan Media Flipbook pada Pelajaran Pendidikan Pancasila untuk Meningkatkan Motivasi Belajar Siswa - Tri Murtiningsih; Sutrisno Wibawa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The purpose of this study was to examine the implementation of the Project Based Learning (PjBL) model integrated with digital learning media in the form of flipbooks to enhance the learning motivation of second-grade students at SD Negeri Jetis in Pancasila Education subject during the 2024/2025 academic year. This study employed a Classroom Action Research (CAR) method with a mixed-method approach combining qualitative and quantitative data. The qualitative method utilized observation sheets and interviews for data collection, while the quantitative method used tests. Each cycle consisted of four stages: planning project-based learning, implementing activities using flipbooks, observing student activities and responses, and reflecting for improvements in the subsequent cycle. The subjects of this study were 28 second-grade students, consisting of 14 male students and 14 female students. The results showed an increase in student learning motivation from cycle I to cycle II, with each cycle consisting of two meetings, where the average motivation score increased from 68.5 to 85.2. Data obtained through interviews and observations indicated that the implementation of the PjBL model supported by digital flipbook media proved effective in enhancing learning enthusiasm, active student engagement in the learning process, and their understanding of Pancasila values. Recommendations for future research include the utilization of digital flipbook learning media to improve student comprehension in Pancasila Education.